Motivasi Pengelola dalam Mendirikan Taman Baca Masyarakat (TBM) di Kabupaten Bandung Barat - Yunus Winoto; Eca Tri Luciana; Rully Khairul Anwar (IJAL (Indonesian Journal of Academic Librarianship), 2019)
This study aims to determine the motivation of managers in establishing community reading parks. This research was conducted at the Community Reading Park in West Bandung Regency. The method used in the study uses a qualitative approach to the type of phenomenological research. The technique of collecting data is done through observation, interviews and through library research. Based on the results of the study, it was revealed that the motives of the manager's goal in establishing TBM were to facilitate the community through TBM, increase public interest in reading and to provide facilities that could benefit the community. As for the motives for the reason for the management to establish TBM is due to lack of information or knowledge of the community, to preserve the reading culture, increase children's knowledge, to limit uncontrolled child association, high rates of illiteracy, and still lack public awareness of the importance of education.